2020
DOI: 10.1101/2020.05.03.20084624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the social distancing privilege gap: a longitudinal study of smartphone movement

Abstract: Background: In response to the coronavirus pandemic, social distancing became a widely deployed countermeasure in March 2020. We examined whether healthier and wealthier places more successfully implemented social distancing. Methods: Mobile device location data were used to quantify declines in movement by county (n=2,633) in the United States of America, comparing April 15-17 (n=65,544,268 traces) to baseline of February 17 - March 7. Negative binomial regression was used to estimate gradients of privilege … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 23 publications
2
39
1
Order By: Relevance
“…Second, we contribute to the small but rapidly growing literature using aggregate GPS data to study the effect of policies trying to contain the spread of COVID-19 on mobility patterns [Allcott et al, 2020, Dasgupta et al, 2020. Using GPS data is one of the main alternatives to using surveys [Briscese et al, 2020, Jørgensen et al, 2020, which likely do not provide reliable data on mobility due to social desirability bias [Daoust et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we contribute to the small but rapidly growing literature using aggregate GPS data to study the effect of policies trying to contain the spread of COVID-19 on mobility patterns [Allcott et al, 2020, Dasgupta et al, 2020. Using GPS data is one of the main alternatives to using surveys [Briscese et al, 2020, Jørgensen et al, 2020, which likely do not provide reliable data on mobility due to social desirability bias [Daoust et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using mobility data have also suggested the potential for inequalities in the ability to practice social distancing based on income 20 , race and education 19 , or on the availability of healthcare providers 21 . However, most of these studies consider these determinants in isolation and do not allow to disentangle the potential additive effects the socioeconomic make-up of counties on the ability of their population to practice social distancing.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the number of users that are included in Colocation Maps, we have decent coverage for most countries in Europe, North America, South America, South Asia and Southeast Asia, but less coverage in other parts of Asia, Africa and Oceania. Figure 4 compares the age distribution of people who are included in Colocation Maps to distributions from the high-resolution settlement layer (HRSL) and from population data from the United Nations (UN) 8 when HRSL is not available. The HRSL is a dataset, built by data scientists at Facebook based only on satellite data, which provides state-of-the-art estimates of population density in many regions of the world [51].…”
Section: Representativenessmentioning
confidence: 99%